2013
DOI: 10.1088/0004-637x/779/2/177
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Stratospheric Temperature and Chemical Composition Over One Titanian Year

Abstract: Since the Voyager 1 (V1) flyby in 1980, Titan's exploration from space and the ground has been ongoing for more than a full revolution of Saturn around the Sun (one Titanian year or 29.5 Earth years had elapsed in 2010 May). In this study, we search for temporal variations affecting Titan's atmospheric thermal and chemical structure within that year. We process Cassini/CIRS data taken during the Titan flybys from 2006-2013 and find a rather uneventful equatorial evolution. Conversely, at northern latitudes, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 46 publications
5
42
0
Order By: Relevance
“…We have already published an analysis of spectra acquired by Cassini/CIRS at high resolution from 2010 onward, both in nadir and limb mode and at high and middle latitudes (Coustenis et al 2013(Coustenis et al , 2016. In our 2016 work, we showed that the hydrocarbons found at high concentrations and longer lifetimes did not show significant latitudinal variability in the past years and until mid-2013.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…We have already published an analysis of spectra acquired by Cassini/CIRS at high resolution from 2010 onward, both in nadir and limb mode and at high and middle latitudes (Coustenis et al 2013(Coustenis et al , 2016. In our 2016 work, we showed that the hydrocarbons found at high concentrations and longer lifetimes did not show significant latitudinal variability in the past years and until mid-2013.…”
Section: Introductionmentioning
confidence: 65%
“…These investigations have shown that a large-scale reversal occurred in the single pole-to-pole circulation affecting the distribution of the atmospheric structure after the northern equinox in mid-2009, with the gases in the summer hemisphere showing upwelling while in the winter pole a corresponding subsidence was found (Achterberg et al 2008(Achterberg et al , 2011Bampasidis et al 2012;Teanby et al 2012). Whereas until 2011 a significant build-up of trace gases, haze, and condensates was still observed over the north pole (West et al 2011(West et al , 2016Jennings et al 2012aJennings et al , 2012bCoustenis et al 2013;Vinatier et al 2015), toward the end of that period, the vortex and hotspot reported in Jennings et al (2015) and Achterberg et al (2008) had practically disappeared. In its place, similar features started to appear near the south pole, which have evolved to what we see today.In the absence of sunlight, gases that subsidize have accumulated since 2012 and become enhanced (e.g., Coustenis et al 2016 and references within;Teanby et al 2017), and a subset of those have been suggested to be causing the haze decrease found in the north and its subsequent increase in the south (Jennings et al 2012b(Jennings et al , 2015.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have been monitoring such emissions since the beginning of the Cassini mission in the focal plane 3 (FP3) of CIRS covering the spectral range from 600 to 1100 cm -1 (Coustenis et al, 2007(Coustenis et al, , 2010(Coustenis et al, , 2013Bampasidis et al, 2012). Focal plane 4 (FP4) is used to extract the temperature profiles from the methane emission in the band centered at 1305 cm -1 .…”
Section: Observations and Analysismentioning
confidence: 99%
“…The middle atmosphere, the stratosphere, showed evolution in temperature and chemical composition during the Cassini mission, especially in the north up to a couple of years ago (e.g. Achterberg et al, 2011;Teanby et al, 2010;Coustenis et al, 2010;Bampasidis et al, 2012;Coustenis et al, 2013). During the recent winter (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009), the northern pole remained in darkness, allowing for photochemical hazes forming in the upper atmosphere to migrate downwards and accumulate in the stratosphere, where a maximum enhancement was observed during the NSE (e.g.…”
Section: Introductionmentioning
confidence: 99%